PASIR DAN JANJANG KOSONG KELAPA SAWIT SEBAGAI STABILITATOR TANAH LEMPUNG TERHADAP KUAT GESER DAN DAYA DUKUNG TANAH - Febri Nepi Suwendi; Fatma Sarie; Okrobianus Hendri; Eka Putri Setiati (INFO-TEKNIK, 2022)
This study used a mixture of clay, sand and Empty fruit bunch of palm oil with the percentage addition of 5%, 7.5%, 10%. The results of physical properties testing carried out on clay taken from Tanjung Sanggalang Village, Central Kahayan District, Pulang Pisau Regency, Central Kalimantan Province. It has values such as, Water Content (w) = 40.77%, Soil Density (γ) = 1.67 gr/cm3, Specific Gravity (Gs) = 2.73, Atterberg limits, namely Liquid Limit = 42.74%, Plastic Limit = 22.68%, Plasticity Index = 20.06%, Shrinkage Limit = 13.15%. According to the USCS classification system, based on the results of the sieve analysis examination, the percentage of material passing sieve no. 200 ( 0.075 mm) is 64.90% > 50% then the soil is a fine grained soil. Based on the Atterberg examination the soil was classified as clayey and included in the CL group with low to moderate plasticity, and according to AASHTO the soil was classified as loamy with loamy soil conditions with moderate to poor conditions and included in group A-7-6 (11) . From the results of the direct shear test of the soil obtained, the shear angle (⌀) = 12.13, cohesion (c) = 0.1406 Kg/ cm2 and the results of the Unconfined Compression test obtained, Unconfined Compression Test (qu) = 0.460 Kg/ cm2 , soil shear cu) = 0.230 kg/ cm2.